Community-Led Ecosystem: A Promising Strategy to Strengthen Person-Centered Geriatric Care in Preventing Age-Related Dependency - Bobrowicz-Campos, E.; Couto, F.; Teixeira-Santos, L.; Apóstolo, J. (Handbook of Research on Health Systems and Organizations for an Aging Society, 2019)
n this chapter, the triangulation analysis of connections between older adults, relevant stakeholders, and community will be made in order to acknowledge the challenges resulting from demographic changes, identify the gaps in current health and social policy in the field of geriatric care, and outline the pathways for joint actions to achieve successful aging. This analysis will also consider health and health equity drivers, highlighting the relevance of the community-led ecosystem in the spreading and scaling up of the person-centered and integrated healthcare model. By focusing on frailty and frailty-related consequences, this chapter will reflect on the need for implementing joint actions that promote health throughout the lifecycle and that empower citizens for informed decision making. It will also discuss the role of modern societies in creating innovative solutions for successful aging.